Language as an expression of national mentality. (Journal of Universal Science Research, 2023)
The article examines the study of the linguistic picture of the world as a derivative of the national mentality. On the basis of crosslanguage comparison, the universality and ethnospecificity of the language world among the English and Uzbek is revealed, and it is also concluded that each language reflects a certain way of perception and structure of the world.